2021
DOI: 10.24235/amwal.v13i1.8373
|View full text |Cite
|
Sign up to set email alerts
|

How is the Transparency of Zakat Management Entities in Indonesia?

Abstract: Zakat is the third pillar of Islam. Zakat must meet the requirements of meeting the nisab. The potential for zakat in Indonesia reaches IDR 233.8 trillion, but its realization has only reached IDR 10.2 trillion. This study aims to measure the transparency index of zakat management entities in three dimensions: financial transparency, management, and programs. This study quantitatively measured using a descriptive approach. Data were collected through questionnaires from zakat management entities, namely Dompet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The government should improve Zakat management for economic development and communal growth, promoting Islamic values and ensuring non-payers' rights and responsibilities. Current laws only regulate sanctions for Zakat money misuse, but following these laws can boost trust in Zakat organizations and improve corporate performance (Bahri et al, 2021). Alkahtani et al (2020) concluded that government financial and non-financial management decisions can support corporate performance and competitiveness, a sustainable competitive position partially mediates government support and corporate success.…”
Section: The Trust Theory Government Role Theory and Government In Za...mentioning
confidence: 99%
See 1 more Smart Citation
“…The government should improve Zakat management for economic development and communal growth, promoting Islamic values and ensuring non-payers' rights and responsibilities. Current laws only regulate sanctions for Zakat money misuse, but following these laws can boost trust in Zakat organizations and improve corporate performance (Bahri et al, 2021). Alkahtani et al (2020) concluded that government financial and non-financial management decisions can support corporate performance and competitiveness, a sustainable competitive position partially mediates government support and corporate success.…”
Section: The Trust Theory Government Role Theory and Government In Za...mentioning
confidence: 99%
“…A high level of public trust in Zakat management institutions can help them fulfill their obligations with a sense of security and comfort (Maciejczyk, 2021). Muzakki will be more likely to be satisfied with a service if it exceeds his expectations (Bahri et al, 2021). The credibility of a Zakat institution is measured by the Muzakki's level of trust in collecting, managing and distributing Zakat.…”
Section: Transparency Accountability Credibility and Zakat Performancementioning
confidence: 99%
“…Tanpa adanya sifat ini, kehancuran perekonomian akan segera tampak. Sikap amanah akan menunjukkan tingginya moral pengelola zakat sehingga BAZ/LAZ akan bisa berjalan dan teksis di masyarakat (Hasanah, 2014;Bahri et al, 2021). Namun, jika yang terjadi sebaliknya otomatis lembaga zakat itu hilang dengan sendirinya karena masyarakat sudah tidak percaya.…”
Section: Pendahuluanunclassified
“…The potential of zakat in Indonesia reaches IDR233.8 trillion, but the realization has only reached IDR10.2 trillion (Bahri et al, 2021). One of the reasons this problem can occur is because muzaqqi believe in something other than channeling their zakat funds through institutions.…”
Section: Introductionmentioning
confidence: 99%